Bahasa dan Kekuasaan dalam Dialog Tokoh Utama pada Film Pendek Lokal Kalimantan Timur Warung Acil Idah: Pendekatan Analisis Wacana Kritis: Language and Power in the Main Character’s Dialogue in East Kalimantan Local Short Movie “Warung Acil Idah”: A Critical Discourse Analysis Approach - Dinar, Latifah (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2025)
This study examines the relationship between language and power within the dialogues of the main character in the East Kalimantan short film Warung Acil Idah. Based on the premise that language serves not only as a communication tool but also as a means of reproducing power, this research aims to describe the implicit and explicit forms of power relations in the main character's speech. A qualitative approach was employed using Norman Fairclough’s Critical Discourse Analysis, focusing on discursive and social practice dimensions through diction choice and communication strategies. Data were collected via documentation and analyzed using the Miles and Huberman interactive model. The results indicate that the main character utilizes linguistic positioning to maintain authority in social relations and reproduce dominant socio-cultural values. Specifically, the character demonstrates subordinative power negotiation when facing high-status individuals (social practice) and authoritative linguistic dominance when interacting with subordinates (discursive practice). The study concludes that linguistic practices in local films reflect both communication dynamics and deep-rooted power structures within society. These findings contribute to the understanding of discursive practices in local media and highlight the relevance of critical discourse approaches in language and culture studies.